A Web-Based Educational Magnetic Resonance Simulator: Design, Implementation and Testing. - Treceño-Fernández, Daniel; Calabia-del-Campo, Juan; Bote-Lorenzo, Miguel L.; Sánchez, Eduardo Gómez; de Luis-García, Rodrigo; Alberola-López, Carlos (Journal of Medical Systems, 2020)
A new web-based education-oriented magnetic resonance (MR) simulator is presented. We have identified the main requirements that this simulator should comply with, so that trainees can face useful practical tasks such as setting the exact slice position and its properties, selecting the correct protocol or fitting the parameters to acquire an image. The tool follows the client-server model. The client contains the interface that mimics the console of a real machine and several of its features. The server stores anatomical models and executes the bulk of the simulation. This cross-platform simulator has been used in two real educational scenarios. The acceptance of the tool has been measured using two criteria, namely, the System Usability Scale and the Likelihood to Recommend, both with satisfactory results. Therefore, we conclude that given the potential of the tool, it may play a relevant role for the training of MRI operators and other involved personnel.